Pengaruh Karakteristik Demografi, Sosial, Ekonomi Terhadap Kesejahteraan Keluarga Produsen Jenang di Desa Rejowinangun Kecamatan Kademangan - Istifadatul Mufidah; Binti Maunah (Universitas 45 Surabaya, 2024)
This thesis research is based on the existence of welfare which is influenced by demographic, social and economic characteristics. Welfare is a state/condition where people can enjoy a prosperous, satisfying life, where technological progress occurs in harmony with environmental quality. So we can see from the demographic, social and economic characteristics of jenang producers whether they are considered prosperous communities or not. The problem formulation in this thesis is: (1) What are the demographic, social and economic characteristics of jenang producing families in Rejowinangun Village? (2) What is the welfare of the families of jenang producers in Rejowinangun Village?(3) Is there an influence of demographic, social and economic characteristics on the welfare of jenang producing families in Rejowinangun Village? (4) How big is the influence of demographic, social and economic characteristics on the welfare of jenang producing families in Rejowinangun Village? .The research approach used in this research is quantitative descriptive and associative. The population for this research is all jenang producers in Rejowinangun Village. Then the technique used in sampling is probability sampling with the snowball sampling technique. The type of research is descriptive and associative. Descriptive to answer problem formulations and associative to answer problems number three and four. The research results show: submitted to jenang producers in Rejowinangun Village, their welfare conditions are in the very high/very good category. Furthermore, based on the results of the hypothesis test, the result obtained is sig = 0.021 (0.021 <0.05) so that it is said that there is a positive and significant influence between demographic, social and economic influences on the welfare of the family of jenang producers, while based on the hypothesis test, a value (R) of 0.771, indicating that the two variables have a strong relationship.the R Square value is 59.5%, while 40.5% is by other factor.